FEATURES OF CREATION OF STAGE VERSIONS «AS WORK» AND «MOTIF OF WORK»: ON THE EXAMPLE OF STORY «ON SUNDAY MORNING DUG DRAUGHT» OF OLGA KOBYLYANSKA - Kukuruza, Nadija (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
The analysis of creation of stage versions from position of changes or to remain of evolvement of the plot of literary text is given in the article. The author fixed the Features of creation of stage versions «as work» and «motif of work»: on the example of story «On Sunday morning dug draught» of Olga Kobylyanska.